Strategi Kantor Sistem Administrasi Manunggal Satu Atap (SAMSAT) Painan Dalam Meningkatkan Pendapatan Pajak Kendaraan Bermotor di Kabupaten Pesisir Selatan - Melyani, Ratih Sri; Putera, Roni Ekha; Koeswara, Hendri; Putra, Roni Ekha (LPPM Universitas Ekasakti, 2022)
This study describes the implementation of the SAMSAT Painan office strategy in increasing motor vehicle tax revenues in Pesisir Selatan Regency. This research is motivated by the motor vehicle tax as a source of regional income which contributes quite a lot to the regional income of Pesisir Selatan Regency. According to the regulation of the Governor of West Sumatra Number 69 of 2014 concerning regional tax revenue sharing, districts in West Sumatra receive 30% of the realization of PKB revenues they collect. This research is important because of the low compliance of taxpayers in Pesisir Selatan Regency. This study uses the theory proposed by kotten which consists of organizational strategy, program strategy, resource strategy and institutional strategy. The method used in this research is a descriptive qualitative method with data collection techniques, namely interviews, observation and documentation. The selection of informants was carried out by a purposive sampling method. The results showed that the SAMSAT Painan office strategy in increasing PKB Revenue in Pesisir Selatan Regency had been going well and had implemented all types of strategies proposed by kotten. Although in the implementation there are several types of strategies that do not work well, such as the implementation of the program which is still uneven, the lack of creative human resources in running the program, especially for UPTD and the lack of facilities and infrastructure provided for taxpayers in paying motor